Individual talker differences in voice-onset-time: Contextual influences - Theodore, Rachel M. (Acoustical Society of America, 2009)
Previous research indicates that talkers differ in phonetically relevant properties of speech, including voice-onset-time (VOT) in word-initial stop consonants; some talkers have characteristically shorter VOTs than others. Previous research also indicates that VOT is robustly affected by contextual influences, including speaking rate and place of articulation. This paper examines whether these contextual influences on VOT are themselves talker-specific. Many tokens of alveolar ∕ti∕ (experiment 1) or labial ∕pi∕ and velar ∕ki∕ (experiment 2) were elicited from talkers across a range of rates. VOT and vowel duration (a metric of rate) were measured for each token. Hierarchical linear modeling analyses showed that (1) VOT increased as rate decreased for all talkers, but the magnitude of the increase varied significantly across talkers; thus the effect of rate on VOT was talker-specific; (2) the talker-specific effect of rate was stable across a change in place of articulation; and (3) for all talkers VOTs were shorter for labial than velar stops, and there was no significant variability in the magnitude of this displacement across talkers; thus the effect of place on VOT was not talker-specific. The implications of these findings for how listeners might accommodate talker differences in VOT during speech perception are discussed.